The Flouting of Conversational Maxims in Short Messages - Idda Astia (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2013)
This study aims to describe how the participants (senders and receivers) flout conversational maxims in short messages. In this study, the source is taken from short messages that are sent via a provider because nowadays most people do communication with others using mobile phone. This study uses Grice’s theory of cooperative principle is used especially the flouting of maxims (maxim of quantity, maxim of quality, maxim of relevance, and maxim of manner). All kinds of those flouting that exist in short messages are analyzed, which are delivered by the participants (senders and receivers). This research uses qualitative descriptive. The utterances produced by the participants, the senders and the receivers, when they were conversing with each others in term of short messages or texting (SMS) were analyzed and described. The data of the research were written data, collected from the utterances, which contain flouting performed by the senders and the receivers in the short messages or texting (SMS). The result of the research shows that in maxim of quantity, they flout by adding more information and giving a little information. In maxim of quality, all of the participants flout it by saying what they believed false. In maxim of relevance, the participants flouted it by saying irrelevant responses. In maxim of manner, moreover, the participants flouted it by saying convoluted words which are extremely long-winded. The conversational maxim are mostly flouted by the participants (sender and receiver) in the short massages is maxim of quantity. It is flouted by adding more information.